INFLUENCE OF WIND EROSION ON THE GENERAL MORPHOGENETIC CHARACTERISTICS OF IRRIGATED SOILS OF THE MIRZACHUL OASIS - М. И. Умаров; Д. А. Гуломжонов; Б. Ҳ. Эштемиров (Galaxy International Interdisciplinary Research Journal, 2023)
This article presents the results of observations of various deflationary processes in irrigated lands in the territory of Mirzachul (Syrdarya and Jizzakh regions).